Penggunaan Teknologi Artificial Intellegence (AI) untuk Meningkatkan Hasil Belajar IPS Siswa SMP - Aris Joko Riyanto; Muhammad Hanif; Nurhadji Nugraha (ASANKA : Journal of Social Science and Education, 2025)
ABSTRACT This research aims to determine whether the use of Artificial Intelligence (AI) can improve students' social studies learning outcomes. The social studies learning outcomes of class 8D students increased after implementing AI-based learning over two cycles, with the following results: (1) In the pre-cycle, students' social studies learning outcomes were in the poor category with an average score of 68.79. Only 11 students (37.93%) achieved the Minimum Mastery Criteria (KKTP). Classically, students did not achieve KKTP in social studies learning; (2) In the first cycle, students' learning outcomes were in the sufficient category with an average score of 74.14. As many as 20 students (68.97%) achieved KKTP. Classically, students did not achieve KKTP in social studies learning; (3) In the second cycle, students' learning outcomes were in the good category, with an average score of 83.10. There were 25 students (86.21%) who successfully achieved KKTP. Classically, students achieved KKTP in social studies learning. Based on the results of data analysis, it can be concluded that the use of AI in social studies learning can improve the social studies learning outcomes of class 8D students at SMP Negeri 12 Madiun. ABSTRAK Penelitian ini bertujuan untuk mengetahui apakah penggunaan Artificial Intelligence (AI) dapat meningkatkan hasil belajar IPS siswa. Hasil belajar IPS siswa kelas 8 D meningkat setelah dilaksanakan pembelajaran dengan menggunakan AI selama 2 siklus dengan hasil sebagai berikut: (1) Hasil belajar IPS siswa pada prasiklus, berada pada kategori kurang dengan nilai rata-rata adalah 68,79. Siswa yang mampu mencapai KKTP sebanyak 11 siswa (37,93%). Secara klasikal siswa tidak mencapai KKTP pada pembelajaran IPS; (2) Hasil belajar IPS siswa pada siklus I berada pada kategori cukup dengan nilai rata-rata adalah 74,14. Siswa yang mencapai KKTP sebanyak 20 siswa (68,97%). Secara klasikal siswa tidak mencapai KKTP pada pembelajaran IPS; (3) Hasil belajar siswa pada siklus II, berada pada kategori baik, dengan nilai rata-rata 83,10. Terdapat 25 siswa (86,21%) yang berhasil mencapai KKTP. Secara klasikal, siswa mencapai KKTP pada pembelajaran IPS. Berdasarkan hasil analisis data dapat disimpulkan bahwa penggunaan AI dalam pembelajaran IPS dapat meningkatkan hasil belajar IPS siswa kelas 8 D SMP Negeri 12 Madiun.